2010
DOI: 10.1017/s0308210508000656
|View full text |Cite
|
Sign up to set email alerts
|

The Lifshitz–Slyozov–Wagner equation for reaction-controlled kinetics

Abstract: Abstract. We rigorously derive a weak form of the Lifshitz-Slyozov-Wagner equation as the homogenization limit of a Stefan-type problem describing reaction-controlled coarsening of a large number of small spherical particles. Moreover, we deduce that the effective mean-field description holds true in the particular limit of vanishing surface-area density of particles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…A stochastic analog of the Becker-Döring model has been investigated 13 and it has been shown that it converges to the deterministic counterpart when the initial magnitude of the monomer units grows large. A further coarsening step can be applied to the deterministic Becker-Döring equation to show their convergence to the Lifshitz-Slyozov model based on a transport partial differential equations 14,15 when the space of the particle sizes id scaled to the continuous. This approach is based on a socalled classical scaling where in the first place only nucleation occurs, and only after a large portion of the monomers has been spent in nucleations, the growths start to take place.…”
Section: Introductionmentioning
confidence: 99%
“…A stochastic analog of the Becker-Döring model has been investigated 13 and it has been shown that it converges to the deterministic counterpart when the initial magnitude of the monomer units grows large. A further coarsening step can be applied to the deterministic Becker-Döring equation to show their convergence to the Lifshitz-Slyozov model based on a transport partial differential equations 14,15 when the space of the particle sizes id scaled to the continuous. This approach is based on a socalled classical scaling where in the first place only nucleation occurs, and only after a large portion of the monomers has been spent in nucleations, the growths start to take place.…”
Section: Introductionmentioning
confidence: 99%
“…Its most common formulation is in terms of an infinite system of ordinary differential equations [17][18][19] . By employing a coarsening step, the discrete space of the particle sizes can be mapped to a continuous limit domain, and consequently the deterministic Becker-Döring model converges to a transport partial differential equation named after Lifshitz-Slyozov 20,21 .…”
Section: Introductionmentioning
confidence: 99%